Atypical MRI features involving the brain in Wilson's disease - Yousaf, Muhammad (Radiol Case Rep, 2015)
Wilson's disease is an inborn error of copper metabolism characterized by inability of the liver to excrete copper into the bile, with excessive deposition of copper primarily in the liver and in the brain. The lentiform nuclei are involved, most often followed by involvement of the thalami, the pons, midbrain, superior and inferior cerebellar peduncles, and the cerebellar nuclei. Predominant involvement of the thalami and brainstem with no significant involvement of the lentiform nuclei is not common. We present a case of Wilson's disease with minimal involvement of the lentiform nuclei, with marked lesions involving the thalami, midbrain, and pons.